Adapting the Bilingual Aphasia Test for West Greenlandic: Issues and alternatives - Limskov, Mikkel Valdemar (Institut for Nordiske Studier og Sprogvidenskab, Københavns Universitet, 2022)
Background: West Greenlandic patients diagnosed with Broca’s aphasia exhibit a non-conventional syndrome, which could be related to certain peculiarities of polysynthetic languages. However, there is currently no acknowledged screening test available for West Greenlandic, which means that the current diagnosis is based on theory founded on dissimilar Western European languages. To advance our understanding of aphasia and improve the therapeutic outlook of West Greenlandic patients, we should adapt one of several available tests for West Greenlandic. Aims: The aim of this article is to provide a preliminary sketch of features of the West Greenlandic dialect that would require added awareness in the event of an adaption due to their contrast with Western European morphology and syntax. Method & procedure: I compared valency and derivational morphology across English and West Greenlandic to demonstrate their differences. Outcomes & results: The expected differences were confirmed. West Greenlandic uses derivational morphology to convey more information than English. Likewise, West Greenlandic also possesses features without equal in the English language. Conclusion: Based on the results, it is safe to say that there exists a need for an adapted test for West Greenlandic patients. The Bilingual Aphasia Test displays significant advantages and should be considered for adaption.